MEDIA PEMBELAJARAN PENGENALAN HEWAN BERBASIS QUIVER: STUDI DESKRIPTIF PADA TK MAWARSARI DI KABUPATEN BARITO KUALA - Rahmi, Nor; Amrullah, Abdul Khair; Maulidha, Maulidha (EDUKIDS : Jurnal Inovasi Pendidikan Anak Usia Dini, 2025)
ABSTRACT Learning activities for introducing animals in early childhood education are still predominantly reliant on conventional, static media, which are less effective in attracting children’s attention and engagement. This condition highlights the need for innovative learning media that are interactive and aligned with the developmental characteristics of young children. This study aims to describe the implementation of augmented reality based learning media for animal introduction using the Quiver application at TK Mawarsari, Barito Kuala Regency. The research employed a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation, involving an early childhood education teacher as the research participant. The implementation of Quiver media was conducted through several stages, namely coloring activities, scanning images using digital devices, and children’s interaction with three-dimensional animal objects. The results indicate that the use of Quiver increases children’s enthusiasm, focus, and active participation during learning activities, as well as helps them understand animal names, shapes, and sounds more concretely. Technical constraints such as limited internet connectivity can be minimized through adequate preparation of learning devices. Therefore, Quiver media can be concluded to be effective in supporting interactive, enjoyable, and meaningful thematic learning for introducing animals in early childhood education. ABSTRAK Pembelajaran pengenalan hewan pada pendidikan anak usia dini masih didominasi penggunaan media konvensional yang bersifat statis, sehingga kurang optimal dalam menarik perhatian dan keterlibatan anak. Kondisi tersebut mendorong perlunya inovasi media pembelajaran yang interaktif serta selaras dengan karakteristik perkembangan anak usia dini. Penelitian ini bertujuan untuk mendeskripsikan penerapan media pembelajaran pengenalan hewan berbasis augmented reality melalui aplikasi Quiver di TK Mawarsari Kabupaten Barito Kuala. Penelitian menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data berupa observasi, wawancara, dan dokumentasi yang melibatkan guru PAUD sebagai partisipan. Penerapan media Quiver dilaksanakan melalui tahapan kegiatan mewarnai gambar, pemindaian menggunakan perangkat digital, serta interaksi anak dengan objek hewan tiga dimensi. Hasil penelitian menunjukkan bahwa penggunaan Quiver mampu meningkatkan antusiasme, fokus, dan partisipasi aktif anak selama pembelajaran, serta membantu anak memahami nama, bentuk, dan suara hewan secara lebih konkret. Kendala teknis seperti keterbatasan jaringan internet dapat diminimalkan melalui persiapan perangkat pembelajaran yang memadai. Dengan demikian, media Quiver dapat disimpulkan efektif sebagai pendukung pembelajaran tematik pengenalan hewan yang interaktif, menyenangkan, dan bermakna bagi anak usia dini.